Konservasi Mata Air Mbarek: Upaya Menjaga Keberlangsungan Hidup - Suparno, Suparno; Markawie, Markawie (Jurnal Teknologi Berkelanjutan, 2024)
This study discusses the conservation efforts of Mbarek Spring in Sumberejo Village, Malang Regency, as a response to the declining water discharge threatening the sustainability of clean water supply. By combining quantitative and qualitative data, the research explores community perceptions and participation, as well as analyzes vegetation around the spring. The results reveal high community appreciation for Mbarek Spring and strong motivation to engage in conservation activities. Recommended management strategies include intensive outreach, establishing village regulations, and developing green areas by planting economically and ecologically beneficial vegetation. By leveraging local wisdom, involving village authorities, and harnessing community enthusiasm, these strategies are expected to enhance the sustainability of water resources and positively impact the local economy.